Microstructure, strain hardening behavior, segregation and corrosion resistance of an electron beam welded thick high-Mn TWIP steel plate - Yong Chen; Guang-Ming Liu; Hua-Ying Li; Xiao-Ming Zhang; Hua Ding (Journal of Materials Research and Technology, 2023)
In the present work, the microstructure, strain hardening behavior, segregation and corrosion resistance of a high-Mn TWIP steel joint fabricated by electron beam welding (EBW) method were investigated. It was observed that in the fusion zone (FZ), columnar dendritic structure and cellular structure were formed and the texture component of ⟨100⟩∥X-axis was developed. Annealing twinning events hardly occurred during the solidification of weld metal since few Ʃ3 and Ʃ9 grain boundaries existed in the FZ. The 0.2% yield strength (YS) of the joint is comparable to that of the base metal (BM). Deformation twinning played an important part in increasing the strain hardening rate. C, Mn and Si elements were found to segregate in the interdendritic regions, nevertheless, Al element was discovered to concentrate in the centres of the dendrites. The microsegregation of alloying elements and the formation of (Fe,Mn)3C cementites increased the corrosion sensitivity of interdendritic regions, which led to the occurrence of preferential corrosion in these regions and then reduced the corrosion resistance of the joint.